Methods for preliminary determination of pemetrexed in macromolecular drug-carrier systems - Ciekot Jarosław; Goszczyński Tomasz Marek; Boratyński Janusz (Acta Pharmaceutica)
Pemetrexed (PMX) is an antifolate drug utilized in the treatment of non-small cell lung cancer. For studies of potential macromolecular carriers for PMX, fast and precise methods were developed to determine the bound and free drug contained in investigated conjugate preparations. The analysis of the total amount of PMX in conjugates was based on absorption spectrophotometry. The linearity was found in the range of 4.697–46.97 μmol L−1 PMX. The limit of quantitation was 1.070 μmol L−1. The method for the analysis of unbound PMX was based on size-exclusion chromatography and detection at 225 nm. This method shows linear range of 2.230–223.0 μmol L−1. LOQ was 0.539 μmol L−1. The proposed methods can be used both for the characterization of the polysaccharide based conjugates of PMX and for the determination of conjugate drug release profiles.